2021
DOI: 10.3390/su132212686
|View full text |Cite
|
Sign up to set email alerts
|

Energy Stored in Above-Ground Biomass Fractions and Model Trees of the Main Coniferous Woody Plants

Abstract: The paper considers energy stored in above-ground biomass fractions and in model trees of the main coniferous woody plants (Picea abies (L.) H. Karst., Abies alba Mill., Pinus sylvestris (L.), Larix decidua Mill.), sampled in 22 forest stands selected in different parts of Slovakia. A total of 43 trees were felled, of which there were 12 spruces, 11 firs, 10 pines, and 10 larches. Gross and net calorific values were determined in samples of wood, bark, small-wood, twigs, and needles. Our results show that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Based on the results of the synchronous thermal analysis, it can be concluded that biomasses of Phragmites australis plants have the most optimal thermal properties. The net calorific value (NCV) of these biomasses is 12.62 MJ/kg, which is comparable to the calorific value of Abies alba wood, which is estimated at 18.9 MJ/kg [34]. A temperature of destruction in the range of 344-351 • C should be considered optimal because, at this temperature, the maximum destruction rate is achieved.…”
Section: Assessment Of the Physicochemical Properties Of Emergent Aqu...mentioning
confidence: 85%
“…Based on the results of the synchronous thermal analysis, it can be concluded that biomasses of Phragmites australis plants have the most optimal thermal properties. The net calorific value (NCV) of these biomasses is 12.62 MJ/kg, which is comparable to the calorific value of Abies alba wood, which is estimated at 18.9 MJ/kg [34]. A temperature of destruction in the range of 344-351 • C should be considered optimal because, at this temperature, the maximum destruction rate is achieved.…”
Section: Assessment Of the Physicochemical Properties Of Emergent Aqu...mentioning
confidence: 85%